2020
DOI: 10.1002/piq.21318
|View full text |Cite
|
Sign up to set email alerts
|

Workforce Resilience: Integrative Review for Human Resource Development

Abstract: Resilience is a concept of growing interest in the modern workplace. Multiple stakeholders, including policy makers, organizational leaders, human‐resource professionals, and employees discuss resilience as an essential element needed to effectively deal with unexpected and mind‐boggling changes that riddle the current workplace. These collective interests are commonly known as workforce resilience. However, there is a lack of consensus as to what causes and entails workforce resilience as well as how to best … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 95 publications
0
13
0
Order By: Relevance
“…While acute stressors such as natural disasters normally elicit trauma responses, the recovery trajectories that follow are contingent on initial appraisals of the stressor and of the existing resources to cope with it. Scholars have recently suggested that individual appraisals of an acute stressor and its impact are likely disaster‐specific, domain‐specific, and the upshot of personal, social, and broader contextual factors (Bader et al, 2019; Fisher et al, 2019; Lim et al, 2020; Yao & Hsieh, 2019). For instance, an individual may perceive a global financial crisis as presenting a very different level of personal risk compared to an earthquake or a disease outbreak, and feel better equipped to deal with or even capitalise on one of these events compared to the others.…”
Section: Resilience In the Workplacementioning
confidence: 99%
See 4 more Smart Citations
“…While acute stressors such as natural disasters normally elicit trauma responses, the recovery trajectories that follow are contingent on initial appraisals of the stressor and of the existing resources to cope with it. Scholars have recently suggested that individual appraisals of an acute stressor and its impact are likely disaster‐specific, domain‐specific, and the upshot of personal, social, and broader contextual factors (Bader et al, 2019; Fisher et al, 2019; Lim et al, 2020; Yao & Hsieh, 2019). For instance, an individual may perceive a global financial crisis as presenting a very different level of personal risk compared to an earthquake or a disease outbreak, and feel better equipped to deal with or even capitalise on one of these events compared to the others.…”
Section: Resilience In the Workplacementioning
confidence: 99%
“…Recent scholarly works offer systematic, multilevel descriptions of resilience‐promoting resources, spanning team, organisational, and extraorganisational levels of analysis (e.g., Hartmann et al, 2020; Hartwig, Clarke, Johnson, & Willis, 2020; Lim et al, 2020). The resources most frequently cited as resilience‐promoting factors that develop capability and effectively address psychosocial risks include teamwork quality, a learning culture, participation in decision‐making, flexibility, role clarity, ongoing feedback, clear organisational communications, peer and leadership support, and developmental opportunities (e.g., Cooke, Cooper, Bartram, Wang, & Mei, 2019; Kuntz et al, 2017; Lim et al, 2020). Carvalho and Areal (2016) submitted a longitudinal analysis of the financial performance of organisations dubbed “best places to work”.…”
Section: Resilience In the Workplacementioning
confidence: 99%
See 3 more Smart Citations